1992
DOI: 10.1177/039139889201501106
|View full text |Cite
|
Sign up to set email alerts
|

Variables Associated with the Assessment of Systemic Tumor Necrosis Factor Alpha Levels during Hemodialysis

Abstract: Conflicting results have been published concerning the systemic induction of the cytokine tumor necrosis factor alpha (TNFα) during hemodialysis (HD). We therefore evaluated in vitro TNFα production in whole blood as well as in vivo variability of TNFα levels in patients on long-term HD. Whole blood was incubated at room temperature (RT) with or without exogenously added endotoxin (ET), and plasma-TNFα was measured after 5, 30, 120, 240, and 960 min by specific enzyme immunoassay. Additionally, plasma-TNFα bef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1997
1997
2003
2003

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…There was no significant difference between the two membranes. Jorres et al [6] observed no significant rise in TNFa levels on either PS or CU membranes or the high inter and intra-individual variability was assigned to the nonstandardized sampling procedures. Rise in circulating TNFa during hemodialysis has been shown in various studies [12,18,19] while others have demonstrated the contrary.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…There was no significant difference between the two membranes. Jorres et al [6] observed no significant rise in TNFa levels on either PS or CU membranes or the high inter and intra-individual variability was assigned to the nonstandardized sampling procedures. Rise in circulating TNFa during hemodialysis has been shown in various studies [12,18,19] while others have demonstrated the contrary.…”
Section: Discussionmentioning
confidence: 96%
“…Samples for IL-1b and TNFa were drawn during the use of a fresh dialyzer in all patients at 0, 15, 240 mt of the dialysis session from the arterial side of the dialysis circuit, plasma separated and stored at À80 C immediately. [6] During each dialysis session (total 240 dialysis sessions) intradialytic clinical symptoms were recorded in the study performa. Cytokine assays were done using ELISA kits (BioSource Int., Inc., USA).…”
Section: Methodsmentioning
confidence: 99%
“…The process of dialysis is also known to cause increases in some cytokines such as TNF-a although changes induced by dialysis vary with the type of membranes used (Cavaillon et al, 1992;Jorres et al, 1992;Nakahama et al, 1992;Ward and Gordon, 1993;Canivet et al, 1994;Halwachs et al, 1994;Leeuwenberg et al, 1994;Pereira et al, 1994). This probably accounts for the higher TNF-a concentrations seen in the anephric patient before treatment with IL-2.…”
Section: Discussionmentioning
confidence: 99%